التهاب السحايا عند الوليد المصاب بالإنتان (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة  250 وليداً مصاباً بالإنتان مقبولاً في شعبة الخديج والوليد في مستشفى الأسد خلال الفترة من 1/4/2008-1/7/2009.بلغت نسبة حدوث التهاب السحايا الجرثومي 12/640 (1.8%) من القبول العام في الشعبة و12/250(4.8%) من مرضى الدراسة ,لم تسجل أي حالة التهاب سحايا جرثومية عند الولدان اللاعرضيين مع إنتان باكر, بينما بلغت النسبة عند الولدان العرضيين مع إنتان باكر وعند الولدان مع إنتان متأخر على التوالي 5/95 (5.2%)و7/110 (6.3%),شكلت كل من الخداجة ونقص وزن الولادة عامل خطر للإصابة بالتهاب السحايا الجرثومي , سيطرت الأعراض العصبية (التثبيط 75% , ضعف المنعكسات 66%,نقص المقوية 58%) عند الولدان مع التهاب السحايا الجرثومي تلاها اضطراب الحرارة واضطرابات التغذية.  هذا ما يوجه إلى ضرورة البزل القطني عند الولدان العرضيين في الإنتان الباكر وعند كل الولدان في الإنتان المتأخر, بينما هو قد يكون غير ضروري عند الولدان اللاعرضيين المصابين بالإنتان الباكر . This study included  250 infected newborns admitted to NICU at Al-Assad University  Hospital in Lattakia between 1/4/2008 and 1/7/2009.The incidence rate of bacterial meningitis was 12/640 (1.8% of all  admissions to NICU) and 12/250 (4.2% of patients under study).There were no cases of bacterial meningitis in  asymptomatic  newborns who had an early infection; the incidence rate was 5/95(5.2% of symptomatic newborns who had an early infection); the incidence rate was 7/110 (6.3% of newborns who have a late infection). Prematurity and low birth weight were risk factors of bacterial meningitis Neurological  manifestations dominated the scene; feeding problems and fever instability were the most common clinical manifestations. In conclusion, we must do lumber puncture as a routine evaluation in symptomatic  neonates  who had an early infection, and all newborns with a late infection; but lumber puncture is not necessary in asymptomatic newborns who had an early infection.